EFFICACY OF HERBAL DRUG IN INDUCING ESTRUS IN DELAYED PUBERTAL DEONI HEIFERS - PATIL, A D; MARKANDEYA, N M; BHIKANE, A U (The Indian Journal of Animal Reproduction, 2023)
Herbal therapies are preferred for treatment of anestrus due to their cheap, safe and efficiency with easy availability. Delayed maturity is the most common reproductive complaint in native descript heifers. Eighteen Deoni heifers were selected for treatment of delayed maturity with herbal heat inducer powder on the basis of gynaeco-clinical examinations. 75.00 per cent heifers responded for the treatment with ovulatory, intermediate type of estrus and six animals conceived with 1.33 services per conception as against nil response in control group. Estimation of haemoglobin, serum protein, serum copper, serum cobalt and serum iron levels revealed significantly higher increase in treatment group. It was concluded that herbal therapy can efficiently induce fertile estrus in delayed cases of maturity in deoni heifers.